Efektivitas Iklan Melalui Whatsapp Blast Terhadap Keputusan Pembelian di Tunas Toyota Cimone - Sutanto, Titania Febriyanti; Saputra, Faisal Tomi; Mirza, Mochammad (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of this study was to measure the effectiveness of advertising through WhatsApp Blast (X) on the purchase decision variable (Y). The results of the t test obtained are that the significance value of the EPIC variable (X) on the purchase decision variable (Y) is 0.00 <0.05, which means that the t value is significant. And for the calculated t value of 5,262> 1,661, it can be concluded that the EPIC variable has a positive and significant effect on purchasing decisions. The effectiveness of advertising via WhatsApp Blast on purchasing decisions at Tunas Toyota Cimone is 22%, while 88% is influenced by other factors not examined in this study. The purpose of this study was to measure the effectiveness of advertising through WhatsApp Blast (X) on the purchase decision variable (Y). The results of the t test obtained are that the significance value of the EPIC variable (X) on the purchase decision variable (Y) is 0.00 <0.05, which means that the t value is significant. And for the calculated t value of 5,262> 1,661, it can be concluded that the EPIC variable has a positive and significant effect on purchasing decisions. The effectiveness of advertising via WhatsApp Blast on purchasing decisions at Tunas Toyota Cimone is 22%, while 88% is influenced by other factors not examined in this study.